Espaço de formação de Coordenadores Pedagógicos: Núcleo Pedagógico da Diretoria Regional de Ensino do Estado de São Paulo - Marangon, Ana Carolina Boaretto (2023)
The main objective of the present research is to identify and understand the potential of the Pedagogical Center of the Regional Education Board as a space for training Pedagogical Coordinators. To this end, it was necessary to undertake a historical journey, from its creation in 1987, to the present day, in order to contextualize to the reader the work developed by this “pedagogical space” of São Paulo State Department of Education, along these years. A Qualitative Research in Education was also carried out with the Coordinating Teachers of the Pedagogical Center (CTPC), currently called Curriculum Specialist Teacher (CET), on the work developed by the Pedagogical Center with regard to the Training of Pedagogical Coordinators, highlighting the Technical Guidelines, Monitoring Training, Collective Pedagogical Work Class Training and Classroom Observation work. Throughout the chapters, we seek to bring theoretical references on the Training of Pedagogical Coordinators, especially the construction of professional identity, the processes of reflection and collaboration, as well as references on Classroom Observation, such as Vera Placco, Laurinda Ramalho and Vera Trevisan (2011, 2012, 2014), Maria Amélia Franco (2008), Lino de Macedo (2002), Dóris Bolzán (2002) and Pedro Reis (2011), as well as documents from the Department of Education itself. The methodology is anchored in theoretical references such as Marli André and Bernardete Gatti (2008), Ludke Menga (1986) and Adriana Ferro Moura (2014), to support the research and dialogue with the data constructed through a questionnaire and conversation circle. In the analysis of the data obtained, categories were created a priori, in the case of the questionnaire, and a posteriori in relation to the conversation circle. The research results indicate the development of a training work by the Pedagogical Center together with the Pedagogical Coordinators, through the Technical Guidelines and mainly in the Training Monitoring carried out by the CTPC and teaching supervisor in the schools, the latter being much more significant and punctual regarding the continued training of the Pedagogical Coordinator. Thus, the results indicate that the Pedagogical Center is a very relevant space for continued training of the Pedagogical Coordinator. Keywords: Pedagogical Coordinator; Pedagogical Center; Training Process.